The Effect of Work Environment, Communication and Compensation on Motivation and Employee Performance Setda Sukoharjo - Gestanasari, Anon (STIE AUB Surakarta)
This study aimed to analyze the influence of the work environment, communication and compensation on the motivation and performance of employees of Secretariat Sukoharjo. The analysis technique used is to use a test instrument that covers the validity and reliability test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis. Hypothesis Test Results The working environment not significant effect on motivation. Communication significant effect on motivation. Compensation significant effect on motivation. Work environment significantly influence employee performance. Communications not significant effect on employee performance. Compensation significant effect on employee performance. Motivation significant effect on employee performance. Test results F on the second equation can be concluded jointly work environment, communication, compensation and motivation affect performance. R2 total value of 0.87 means that the performance of Employees in the Secretariat of Sukoharjo explained by the variable working environment, Communication, Compensation and motivation by 87% and the remaining 13% described other variables outside the model study as an example of organizational culture, organizational climate. Results of path analysis showed that of the direct and indirect effects of the conclusion that the direct influence of the working environment and effective significant influence on the performance, is the most dominant influence.KeywordsÂ Â : Work Environment, Communication, Compensation, Motivation, Employee Performance